2005
DOI: 10.1002/chem.200400971
|View full text |Cite
|
Sign up to set email alerts
|

CoI‐ and Co0‐Bipyridine Complexes Obtained by Reduction of CoBr2bpy: Electrochemical Behaviour and Investigation of Their Reactions with Aromatic Halides and Vinylic Acetates

Abstract: The electrochemical behaviour of CoBr(2)bpy (bpy=2,2'-bipyridine) catalyst precursor in acetonitrile has been studied, revealing its possible reduction into the corresponding Co(I) and Co(0) complexes. These low-valent cobalt species appear to be stable on the time scale of cyclic voltammetry. In the presence of aromatic halides, both complexes undergo oxidative addition, the latter Co(0) species allowing the activation of poorly reactive aromatic chlorides. The arylcobalt(III) and arylcobalt(II) obtained are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 22 publications
0
25
0
1
Order By: Relevance
“…This competitive situation was also encountered in the CoBr 2 bpy catalyzed vinylation of aromatic halides, where the vinyl acetate both stabilized the Co(I) complex and reacted on the arylcobalt(II) intermediate. These examples displaying competitive reactions illustrate the unique capacity of cyclic voltammetry in providing fast, quantitative and unambiguous information on the nature and kinetics of follow‐up reactions, thus allowing to establish mechanisms from consolidated data.…”
Section: Electrochemical Characterization Of Complex Reaction Sequencmentioning
confidence: 85%
See 2 more Smart Citations
“…This competitive situation was also encountered in the CoBr 2 bpy catalyzed vinylation of aromatic halides, where the vinyl acetate both stabilized the Co(I) complex and reacted on the arylcobalt(II) intermediate. These examples displaying competitive reactions illustrate the unique capacity of cyclic voltammetry in providing fast, quantitative and unambiguous information on the nature and kinetics of follow‐up reactions, thus allowing to establish mechanisms from consolidated data.…”
Section: Electrochemical Characterization Of Complex Reaction Sequencmentioning
confidence: 85%
“…Interestingly, the cobalt(I) species was also found to be stabilized by more classical ligands such as bipyridine, but through an unusual 1/1 metal/ligand stoichiometry. The electrochemical behavior of CoBr 2 bpy revealed the possibility to generate both Co I and Co 0 redox states in acetonitrile, the latter being stable only over few seconds . Note that such Co 0 ‐bipyridine complexes cannot be obtained from the stable Co(bpy) 3 2+ precursor which is generally preferred to carry out academic electroanalytical studies.…”
Section: Electrochemical Determination Of the Redox State Stability mentioning
confidence: 99%
See 1 more Smart Citation
“…The filtration of arylzinc‐containing solutions was carried with Interchim PTFE syringe filters UptiDisc 22 mm, 0.45 µm. CoBr 2 (bpy) and CoBr 2 (phen) were prepared according to Labbé and Buriez . CoBr 2 (PPh 3 ) 2 was prepared according to Cotton and Holm .…”
Section: Methodsmentioning
confidence: 99%
“…More recently, it was reported that CoBr2 in the presence of a single equivalent of 2,2'-bipyridine or pyridine exhibits a high catalytic activity toward the reduction of aromatic halides [41,42]. In an aqueous solution containing a surfactant, the reduced tris-complex was stabilized in the micelle and a mild kinetic enhancement was reported in the catalytic reduction of allyl halides by the Co(bpy)3 + complex.…”
Section: Introductionmentioning
confidence: 99%